PROPANE-PROPYLENE OLIGOMERIZATION OVER MODIFIED PILLARED CLAY CATALYSTS - R. Toktassyn,; M. Myrzahanov,; E. Markayev, (Academic Scientific Journal of Chemistry, 2019)
Metal supported pillared clay catalysts were used in propane-propylene oligomerization. In the article was shown that the pillaring process has a significant impact on the carrier's nature. That is, specific surface area and porosity of the pillared clay were significantly increase compared with natural clay. The natural clay has lost its porosity at a temperature of 140 °C, reduce surface area from 62 to 20 m2 /g. After pillaring this value increased to 110 m2 /g. The catalysts exhibited good thermal stability at the calcination of 500 to 600 °C as indicated by its specific surface area. As well as, all synthesized catalysts showed selectivity to C6 and C9 olefins. The resulting mixtures of isoolefins provide a high-octane product that can be used as a mixture of environmentally friendly gasoline, jet and diesel fuel through hydrogenation.